MICROPLASTICS IN BIOTIC AND ENVIRONMENTAL SAMPLES TAKEN NEAR TWO MUNICIPAL WASTEWATER TREATMENTS PLANTS IN THE GRAND RIVER, ONTARIO - Weir, Ellie (My University, 2021)
Microplastics are present in municipal wastewater treatment plant (WWTP) effluents; however, it is unclear whether these contaminants are ingested by biota living downstream of these outfalls. This study examined whether microplastic levels in caged biota, resident fish, and environmental samples were elevated near the Waterloo and Kitchener WWTP outfalls along the Grand River in the fall of 2019. Amphipods (Hyalella azteca), fluted-shell mussels (Lasmigona costata), and rainbow trout (Oncorhynchus mykiss) were caged at one upstream reference site and two impacted sites downstream of the Kitchener WWTP for 14 (amphipods and trout) or 28 (mussels) days. Rainbow darter (Etheostoma caeruleum) were collected using a backpack electrofisher from 10 sites up and downstream of both the Kitchener and Waterloo WWTPs, along with surface water and sediment samples. Whole body Hyalella, fish digestive tracts, and fluted-shell mussel tissues (hemolymph, digestive glands, and gills) were digested in 20% potassium hydroxide. Environmental samples were processed using filtration and density separation, then visual identification of microplastics was done. Elevated particle counts were found in rainbow trout digestive tracts at the Kitchener outfall site, compared to the upstream reference and downstream farfield sites. Additionally, particle concentrations in sediment were significantly higher at the Waterloo outfall, compared to all other sites (except for one upstream location). However, whole Hyalella, fluted-shell mussel tissues (hemolymph, digestive glands, and gills), digestive tracts of rainbow darter, and surface waters did not show elevated counts downstream of these discharges. Across all samples, fibers were the most common morphology, and blue and clear particles were prevalent in samples collected near WWTPs. Overall, these findings suggest that the Kitchener and Waterloo WWTPs could be important sources of particles to the Grand River, adding to our understanding of the fate of this contaminant in freshwater ecosystems.
Keywords: Microplastics; Grand River; Municipal Wastewater Effluent; Environmental Contaminants; Ecotoxicology; Environmental Pollution